2021
DOI: 10.1109/access.2021.3067042
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information & Communication Technology in Elearning Environments: A Systematic Review

Abstract: The role of information and communication technology (ICT) in education continues to serve the development of teaching and learning for most subjects, and the subject of Islamic studies is no exception. However, to date, a systematic literature review (SLR) on the role of ICT for this particular subject is lacking. Therefore, to facilitate the implementation and adoption of ICT, we focus on e-learning for the majority of subjects, including Islamic education and ICT applications, e.g. educational software and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 47 publications
0
19
0
1
Order By: Relevance
“…COVID-19 lockdowns have restricted movement, and people have canceled their travel plans, which has impacted the transportation sector as well [39,40]. Recent research has examined the inequalities in learning resulting from digital discrimination during COVID-19, and it showed that students are receiving unbalanced learning chances because of it and fall into mental distress [41][42][43][44]. When schools are not open, and children are being told to stay indoors, their mental health may be negatively impacted in many ways.…”
Section: Related Workmentioning
confidence: 99%
“…COVID-19 lockdowns have restricted movement, and people have canceled their travel plans, which has impacted the transportation sector as well [39,40]. Recent research has examined the inequalities in learning resulting from digital discrimination during COVID-19, and it showed that students are receiving unbalanced learning chances because of it and fall into mental distress [41][42][43][44]. When schools are not open, and children are being told to stay indoors, their mental health may be negatively impacted in many ways.…”
Section: Related Workmentioning
confidence: 99%
“…The highly rapid development in the field of Information and Communication Technology has also given a significant impact and change to the national education system (Setati-Legodi & Goosen, 2022;Sayaf et al, 2021). The field of Information and Communication Technology has opened up opportunities and given different and new challenges to teachers and students in improving the practice of teaching and facilitation process and increasing the effectiveness of learning compared to traditional teaching and facilitation practices that have long been practised (Olimov & Mamurova, 2022;Qazi et al, 2021). Recognizing the fact that teachers also play an important role in implementing effective and quality teaching and facilitation processes, and can provide a positive impact, then teachers should prepare themselves with in-depth knowledge, especially in terms of knowledge relevant to the content of the subjects taught, effective control and delivery methods (pedagogy) as well as mastery to apply technology in the classroom (Akhmedov, 2022;Erbas et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Distance learning has revolutionized education; the terminology describes many types of teaching situations ( Jowsey, 2020 , Qazi, 2021 )The use of distance learning dates back to the use of correspondence based studies in Europe ( Valentine, 2002 , Diacopoulos and Crompton, 2020 ). However, the emergence of the internet and online learning applications such as Zoom, Microsoft teams, Google classroom, and others has revolutionized distance learning protocols in online teaching using the internet.…”
Section: Introductionmentioning
confidence: 99%